Prehospital paediatric emergencies in Belgium: an epidemiologic study. (April 2015) - Houtekie, Laurent; Meert, Philippe; Thys, Frédéric; Guy-Viterbo, Vanessa; Clement de Clety, Stéphan
Abstract : Objectives: In Belgium, emergency medical services (EMS) are staffed with a medical team if mandatory according to the regulation authority procedures. Children are involved in interventions, but no extensive data are available in the country. We analysed the characteristics of the children involved in EMS to gain better knowledge of the pathologies and the needs of these patients. Materials and methods: A retrospective review of all patients under 16 years of age dealt with by our EMS team during a 2-year period. Results: During the 2010–2011 period, our EMS performed 229 paediatric missions. Most of the patients (76.0%) presented medical conditions. Seizure was the most common diagnosis (34.1%), including febrile convulsions in 55.1% of the cases. Five patients (2.2%) suffered a cardiac arrest. All of them died despite advanced life support. Two more patients died before or just after admission to the emergency room. In the subgroup of patients admitted to our hospital, 26.6% needed drug administration and 43.2% were discharged home after emergency room management. Conclusion: Prehospital paediatric emergencies are rarely life-threatening conditions and seldom need advanced medical interventions. However, the outcome of real life-threatening conditions is poor, therefore emphasizing the need for better trained teams.